2021
DOI: 10.3390/curroncol28030156
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Outcomes of Oropharyngeal Squamous Cell Carcinoma Patients after Distant Failure According to p16 Status: Implication in Therapeutic Options

Abstract: Introduction: Recent modifications in the epidemiology of oropharyngeal squamous cell carcinoma (OSCC) have led to the increase of Human papillomavirus (HPV) related metastatic head and neck cancer patients with high life expectancy even at advanced stage, low comorbidity and still restricted systemic therapy opportunities. In the recent era of ablative therapies’ development, oligometastatic HPV OSCC patients are indubitably good candidates for intensified treatment. However, data related to outcomes after op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Because patients with HPV-OPSCCs have better outcomes than those with non-HPV-related tumors (5,23), survival is longer, and treatment tolerance and QoL have become an increasing issue (24). Notably, all patients from our study received IMRT, as it was proven to reduce the incidence of xerostomia and improve saliva-related QoL compared to 3D RT (25,26).…”
Section: Discussionmentioning
confidence: 96%
“…Because patients with HPV-OPSCCs have better outcomes than those with non-HPV-related tumors (5,23), survival is longer, and treatment tolerance and QoL have become an increasing issue (24). Notably, all patients from our study received IMRT, as it was proven to reduce the incidence of xerostomia and improve saliva-related QoL compared to 3D RT (25,26).…”
Section: Discussionmentioning
confidence: 96%
“…Because patients with HPV-OPSCCs have better outcomes compared to those with non-HPV-related tumors [ 5 , 23 ], the issue of treatment tolerance and QoL has become increasingly important [ 24 ]. Notably, all patients from our study received IMRT, as it has been demonstrated to reduce the incidence of xerostomia and improve saliva-related QoL compared to 3D RT [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…27 Patients with HPV-related oropharynx oligometastatic HNSCC have better OS and disease-free survival than HPVÀ counterparts (2-year OS, 60% vs. 25%, p < .05). 28,29 Lee et al 30 showed that patients with metachronous oligometastatic HPV1 oropharynx carcinoma will benefit from initial definitive metastasis-directed therapy compared with upfront systemic therapy (median OS not reached vs. 40.7 months, p 5 .021). Similarly, patients with Epstein-Barr virus-associated oligometastatic nasopharyngeal carcinoma may benefit from long-term control by combining chemotherapy with local radiation therapy to the metastatic lesions.…”
Section: Second-line Therapymentioning
confidence: 99%